Analisis Pengaruh Pengeluaran Pemerintah Sektor Pendidikan, Dan Tingkat Pengangguran Terhadap Pertumbuhan Ekonomi Di Kabupaten/Kota Provinsi Lampung Tahun 2015-2022 - Naufalia Fauzianti; I Wayan Suparta (STIE Amkop Makassar, 2024)
This research aims to analyze the influence of government spending in the education sector and the unemployment rate on economic growth in the district of Lampung Province during 2015 to 2022. This research uses several variables, namely the independent variable consisting of government spending in the education sector (PDK) and unemployment rate (TP), as well as the dependent variable, namely economic growth of districts in Lampung in the 2015-2022 period. The data used is secondary data obtained from government websites and panel data regression method is used to analyze it, using the Eviews10 application. The research results show that the government expenditure variable in the education sector has a positive and significant influence on economic growth in the districts of Lampung Province. This means that increasing government spending in the education sector will encourage economic growth. On the other hand, the unemployment rate variable has a negative and significant influence on economic growth, which means that an increase in the unemployment rate will reduce economic growth. This study hoped that the results of this research can become a reference for further research and enrich knowledge, especially in the study of economic growth in Lampung Province.